Spontaneous pneumothorax with coronavirus disease 2019 in non-ventilated patients: A single-center retrospective case series. (December 2021) - Kawachi, Jun; Koyama, Hiroshi; Aida, Yoshihisa; Kamio, Tadashi; Yamagami, Hiroshi; Nishiguchi, Sho
Abstract: Background: Pneumothorax is a rare complication of coronavirus disease 2019, and many of its associated factors are related to mechanical ventilation. We investigated the incidence and clinical features of patients with pneumothorax and coronavirus disease 2019 at a field hospital for patients who did not require intubation. Materials and methods: An isolated field hospital for COVID-19 patients who did not require ventilation was constructed. Patients who developed pneumothorax were extracted and reviewed retrospectively. Results: Between May 2020 and February 2021, 1061 patients were admitted to this field hospital. Among them, eight patients (0.75%, three men and four women) developed pneumothorax. The mean age at incidence was 79.9 (range: 20–96) years; all patients were over the age of 80 years, except one 20-year-old woman. Six of these eight patients (75%) died. Conclusion: Although pneumothorax is a rare complication of coronavirus disease-2019, it is predictive of a poor prognosis in older-adult patients. Highlights: Incidence of pneumothorax in patients without mechanical ventilation was 0.75%. The mean age was 79.9 years and six of eight (75%) died. Pneumothorax is rare and predictive of poor prognosis patients with COVID-19.